GAYA HIDUP, RELIGIUSITAS DAN LITERASI KEUANGAN SYARIAH TERHADAP KEPUTUSAN PENGGUNAAN E-WALLET LINKAJA SYARIAH PADA MASYARAKAT KOTA SURAKARTA - Juliyanti, Wiwin (AMAL: Jurnal Ekonomi Syariah, 2024)
This study aims to analyze the influence of lifestyle, religiosity, and financial literacy on the decision to use LinkAja Syariah e-wallet in Surakarta City. A quantitative survey method was employed with a sample of 175 respondents who use LinkAja Syariah e-wallet. Data were collected through questionnaires and analyzed using multiple linear regression analysis with E-Views software. The results show that lifestyle, religiosity, and financial literacy significantly affect the decision to use LinkAja Syariah e-wallet, both partially and simultaneously. These findings highlight the importance of these factors in shaping the public’s preference for using a Sharia-compliant e-wallet. The study provides implications for LinkAja Syariah and related parties to continue developing services aligned with Sharia principles and the digital lifestyle of society.